Developing Character of Disability Students through Picture and Picture Models with Sad Dharma Method - Saridewi, Desak Putu; Mahendra, I Wayan Eka (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed at describing picture and picture model in building the character of diffable student’s effort was to strengthen their character, physiological and psychological i.e. building character for students with a special need. This type of research was descriptive qualitative analysis. The technique of collecting data was conducted through in-depth interviews, direct observation in the learning process and study documents. The research subject was diffable students in preparation level and objecting to the activity and student’s affective behavior in the learning process. The result of this research showed the implementation of picture and picture model with Sad Dharma method was yet obtained a good result, proved by almost 67% of students overcome changing behavior, 20% unchanging behavior and 11% of students with apathetic behavior. The model application can be concluded that the level of success on character norm implantation for students with disability, it gave better development, it meant that there was behavior change which needs direction in the beginning in conveying saraswati devotion, tri sandya, praying, berjava and able to do it by themselves and children acts was not interfered by their friends during the learning process.